2021
DOI: 10.3389/fonc.2021.699127
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter MRI Model With DCE-MRI, DWI, and Synthetic MRI Improves the Diagnostic Performance of BI-RADS 4 Lesions

Abstract: ObjectivesTo evaluate the value of synthetic magnetic resonance imaging (syMRI), diffusion-weighted imaging (DWI), DCE-MRI, and clinical features in breast imaging–reporting and data system (BI-RADS) 4 lesions, and develop an efficient method to help patients avoid unnecessary biopsy.MethodsA total of 75 patients with breast diseases classified as BI-RADS 4 (45 with malignant lesions and 30 with benign lesions) were prospectively enrolled in this study. T1-weighted imaging (T1WI), T2WI, DWI, and syMRI were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The ADC _min value of malignant lesions was lower than that of benign lesions, which was the same as the previous research results [ 26 ]. This might be attributed to the continuous proliferation of tumor cells, the increase in the synthesis of macromolecular substances in the cytoplasm, the release of a large amount of necrotic substances, the reduction of extracellular space, the increase of bound water content, and the restricted diffusion of free water molecules [ 27 ]. A meta-analysis showed that the ADC value for distinguishing between benign and malignant breast lesions range from 0.92 to 1.61 × 10 −3 mm 2 /s [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ADC _min value of malignant lesions was lower than that of benign lesions, which was the same as the previous research results [ 26 ]. This might be attributed to the continuous proliferation of tumor cells, the increase in the synthesis of macromolecular substances in the cytoplasm, the release of a large amount of necrotic substances, the reduction of extracellular space, the increase of bound water content, and the restricted diffusion of free water molecules [ 27 ]. A meta-analysis showed that the ADC value for distinguishing between benign and malignant breast lesions range from 0.92 to 1.61 × 10 −3 mm 2 /s [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many groups have also found significant differences of ADC values between benign and metastatic breast lymph nodes ( 62 64 ), however, their diagnostic performance in differentiating these lymph nodes still need further investigation ( 64 ) compared to simpler markers such as the lymph node size. Quantitative DWI in addition to DCE‐MRI and other plain MRI such as T1WI and T2WI also leads to improved diagnostic performance, in terms of specificity for BI-RADS (Breast Imaging-Reporting And Data System) 3 and 4 lesions, or evaluating malignancies with BI-RADS 4 lesions ( 65 , 66 ).…”
Section: Breast Diffusion Mrimentioning
confidence: 99%
“…PTs that do not have typical malignant signs but sufficient suspicious manifestations should be classified as BI-RADS IV. PTs exhibit different time-signal intensity curve (TIC) types (10,11). The TICs exhibited by benign PTs may be similar to FAs, while the TICs exhibited by borderline and malignant PTs may be similar to breast cancers (BCs).…”
Section: Introductionmentioning
confidence: 99%